[Rezension von: Young, Frances M., 1939-, Doctrine and scripture in early Christianity. volume one, Scripture, the genesis of doctrine] - Bockmuehl, Markus (Journal of Anglican studies, 2025)
Frances M. Young, Scripture, the Genesis of Doctrine. Doctrine and Scripture in Early Christianity l. Eerdmans, Grand Rapids, Michigan. 2023. Hbk.pp.xxvii+280. $40.99. ISBN 9780802882981 - Volume 23 Issue 1